Bolero Film e Grand Hotel: Declinazioni liminali di identità di genere nella scrittura scenica di Francesco Saponaro - Zinno, Angela (Mimesis Journal, 2024)
The essay focuses on one of the fundamental points of Enzo Moscato’s literature (poetics of transsexualism) investigated through the creative process that generates the staging. In particular, the work of the director Francesco Saponaro about Ragazze sole con qualche esperienza (written by Moscato in 1985) is analyzed with special attention in observing the main characters as declinations of gender identity. A circular path that – starting from charac- ters such as Bolero Film and Grand Hotel as staging by Saponaro in 2017 – analyzes the directorial / dramaturgical vision that conveys and mutates into a ‘scenic key’ the intrinsic paradigms of Enzo Moscato’s dramaturgy.